Kunjungan Industri sebagai Media Pembelajaran Manajemen Mahasiswa di PT Amerta Indah Otsuka (Studi pada Kegiatan Kunjungan Industri Himpunan Mahasiswa Manajemen Universitas Pamulang Tahun 2026) - Tamala Setiarini; Panji Prasetyo; Khansa Nadifah Azzahra; Maida Fariha; Fardhan Ghazalah (CV. ITTC INDONESIA, 2026)
This article discusses the implementation of an industrial visit organized by the Management Students Association (HMM) of Pamulang University to PT Amerta Indah Otsuka on July 27, 2026, involving 59 students. This activity was designed using the experiantal learning method so that students could observe firsthand the application of business strategies and operational management in the manufacturing industry. Data collection of the activites. The result of the observations indicate that this activity helped students understand the connection between management theories learned in the classroom and real-world practices, particularly regarding quality control and standard operating procedures. In addition to producing an activity report and publications, this activity is expected to mark the beginning of ongoing collaboration between the university and industry.